Assessment of water fluxes under the dual threat of changes in land cover and climate variability in the Brazilian Cerrado biome - Dimaghi Schwamback; Abderraman R. Amorim Brandão; Ronny Berndtsson; Edson Wendland; Magnus Persson (Journal of Hydrology: Regional Studies)
Study region: The Brazilian wooded Cerrado biome is a tropical savanna, over 50 % of which has been converted to agricultural land. Study focus: We evaluated changes in water balance variables (surface flux, evaporation, soil-water storage, infiltration, groundwater recharge, and root uptake) due to climate change. The study included (i) calibration and validation of the Hydrus model through observations of soil moisture in experimental plots covered with sugarcane and pasture compared to natural forest during six years and (ii) hydrological predictions by combining Hydrus with projections from climate models (10 CMIP6 models under SSP2–4.5 and SSP5–8.5 scenarios). New hydrological insights for the region: We tested different parameter combinations during calibration and found that for sugarcane and pasture, saturated soil water content, parameter N in the soil retention function, and saturated hydraulic conductivity were the most sensitive ones to improve calibration. The validated models demonstrated good performance, with a mass balance error of less than 0.9 %. The results indicate that climate change will affect certain water fluxes more than others, in a hierarchical (bottom-top) sequence: soil-water storage, bottom flux, infiltration, surface flux, evaporation, and root uptake. For example, root uptake is expected to increase by 26 % in sugarcane and pasture crops at the end of 2100, pressuring water regional demand. Lastly, land cover change currently poses a greater risk to water fluxes than projected climate change.